AI and the Future of Library Accessibility: Making Digital Promotions Inclusive - Hariyani Putri, Soraya, Ms; Adiba, Syifa, Ms (UI Scholars Hub, 2024)
The rise of artificial intelligence (AI) has transformed various sectors, including the field of library and information science. Libraries, as custodians of knowledge and cultural heritage, are increasingly utilizing AI to enhance their services, particularly in the realm of digital promotions. However, there remains a significant challenge in making these promotions accessible to all users, especially those with disabilities. Despite advancements in AI, digital content produced by libraries often lacks inclusivity, particularly in catering to the needs of users with disabilities. This gap not only limits access to library services but also hinders the broader mission of libraries to serve diverse communities. This study aims to explore how AI can be leveraged by librarians to create more inclusive and accessible digital promotions. By examining the current practices of digital promotion on social media platforms such as Instagram and X by the National Library of Indonesia, this research seeks to identify effective strategies that can be adopted to enhance accessibility. Given the increasing reliance on digital platforms for outreach and engagement, ensuring that library promotions are inclusive is vital. This research is significant as it provides insights into how AI can be a powerful tool in bridging the accessibility gap, thereby enabling libraries to better serve all users, including those with disabilities. The study employs a qualitative approach, utilizing observation and literature review as primary data collection methods. It involves a comparative analysis of digital promotions on Instagram and X by the National Library of Indonesia and other similar accounts to assess the effectiveness of AI-driven accessibility features. Preliminary findings suggest that AI can significantly enhance the 95 accessibility of digital content by enabling the creation of more user-friendly and inclusive promotions. AI tools can assist librarians in translating content into sign language, generating audio descriptions, and tailoring content to meet the specific needs of users with disabilities. This research contributes to the growing body of knowledge on the intersection of AI and library science by demonstrating the potential of AI in creating inclusive digital environments. It highlights the importance of integrating AI in digital promotions to ensure that libraries remain accessible and relevant to all users.